Makna Simbolik Ibadah Haji Perspektif Ali Syariati - Ahmad Fauzan (Islamic Review: Jurnal Riset dan Kajian Keislaman, 2022)
In this study, the author wants to reveal the secret of the meaning of the rituals of Hajj according to Ali Shariati with a philosophical approach. The results of the study explain that the essence of the Hajj ritual according to Ali Shariati is the existential evolution of humans towards God, which is a symbolic drama of the philosophy of the creation of Adam's children and grandchildren. The symbols in the Hajj ritual include the Miqat is a symbol of liberation from selfishness, Ihram is a symbol of purity and equality, the Kaaba is a symbol of God's decree and immortality, Black Stone is a symbol of the oath of allegiance, Maqam Ibrahim is a symbol of historical reality, Sa' i is a symbol of optimism in life, Arafah is a symbol of knowledge and wisdom, Masy'aril haram (Muzdalifah) is a symbol of awareness and intuition, Mina is a symbol of love and martyrdom, Throwing Jumrah is a symbol of jihad against the trinity of kabilism, Cutting hair (tahallul) is a symbol of human gratitude, and Kurban is a symbol of absolute surrender and the fusion of hayawaniyah nature.